2005
DOI: 10.1021/la048303k
|View full text |Cite
|
Sign up to set email alerts
|

Regiospecific Control of Protein Expression in Cells Cultured on Two-Component Counter Gradients of Extracellular Matrix Proteins

Abstract: This work describes the use of microfluidic tools to generate covalently immobilized counter gradients of extracellular matrix (ECM) proteins laminin and collagen I. Using these platforms, we demonstrate control of the expression levels of two proteins linked to cell cycle progression by virtue of the spatial location of cells on the gradients, and hence by the local ECM environments in these devices. In contrast to physisorbed gradients, covalently immobilized protein patterns preserved the gradient fidelity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 23 publications
1
48
0
Order By: Relevance
“…84 Gunawan and co-workers used gradients of extracellular matrix proteins (laminin and collagen I) created in microfluidic networks to demonstrate control over the expression levels of two proteins linked to cell cycle progression by virtue of the spatial location of cells on the gradients. 156,157 A microfluidic setup was recently used to vary the pH of solution gradually, which enabled a dynamic nonequilibrium study of the self-assembly of collagen molecules. 158 A few exotic types of gradients were created by varying external fields, such as temperature, [159][160][161][162] pH, 99,163 and electrochemical potential.…”
Section: Gradient Temporal Dependencymentioning
confidence: 99%
See 1 more Smart Citation
“…84 Gunawan and co-workers used gradients of extracellular matrix proteins (laminin and collagen I) created in microfluidic networks to demonstrate control over the expression levels of two proteins linked to cell cycle progression by virtue of the spatial location of cells on the gradients. 156,157 A microfluidic setup was recently used to vary the pH of solution gradually, which enabled a dynamic nonequilibrium study of the self-assembly of collagen molecules. 158 A few exotic types of gradients were created by varying external fields, such as temperature, [159][160][161][162] pH, 99,163 and electrochemical potential.…”
Section: Gradient Temporal Dependencymentioning
confidence: 99%
“…biotin). 10,24,123,156,149,217,226,[229][230][231][232][233][234][235][236][237][238][239][240] In addition, surface-bound gradients have also been used to investigate systematically platelet adhesion, 241,242 enzyme immobilization, 243 cell adhesion ( Figures 15 and 16), 11,21,31,64,65,[72][73][74]108,117,118,139,140,142,150,235,[244][245][246][247][248][249][250][251][252][253][254][255][256][257][258]…”
Section: Screening a Phenomenonmentioning
confidence: 99%
“…To achieve this, carboxy-terminated beads were activated to bind primary amines of acrylamide through 1-ethyl-3-[3-dimethylaminopropyl]carbodiimide hydrochloride (EDC)/N-hydroxy-succinimide ester (NHS) coupling chemistry. 8 Initial tests showed that activated beads added directly to the gelation mixture interfered with the polymerization. This was avoided by first activating beads with EDC/NHS.…”
Section: Microbead Preparationmentioning
confidence: 99%
“…[4][5][6][7] However, current microfluidic approaches for cell study focus on culturing cells on glass or plastic substrates with gradients of diffusible proteins or surface-bound biomolecules. [8][9][10][11] In native tissues, cells always interact with the surrounding microenvironment with various biophysical properties. 12,13 So, it is preferred to use more physiological cell culture substrate to better mimic the natural cell microenvironment.…”
Section: Introductionmentioning
confidence: 99%